2014
DOI: 10.1016/s2213-2600(14)70069-4
|View full text |Cite|
|
Sign up to set email alerts
|

Lung microbiome and disease progression in idiopathic pulmonary fibrosis: an analysis of the COMET study

Abstract: Background The lung microbiome’s contribution to IPF pathogenesisis unknown. Using COMET-IPF (Correlating Outcomes with biochemical Markers to Estimate Time-progression in Idiopathic Pulmonary Fibrosis), the goal of this study was to determine whether unique microbial signatures would associate with disease progression. Methods IPF subjects within four years of diagnosis aged 35–80 were eligible for inclusion. Subjects were followed for up to a maximum of 80 weeks. This completed observational study is regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
311
5
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 347 publications
(334 citation statements)
references
References 39 publications
8
311
5
4
Order By: Relevance
“…Although the most frequently isolated bacterial species (Prevotella, Veillonella and Escherichia) coincided in part with those identified by MOLYNEAUX et al [25], the authors also observed a new element: a strong association between the presence of specific species of Streptococcus and Staphylococcus and disease progression [28].…”
Section: Ipf and Host-microbiota Interactions And Potential Effects supporting
confidence: 55%
See 1 more Smart Citation
“…Although the most frequently isolated bacterial species (Prevotella, Veillonella and Escherichia) coincided in part with those identified by MOLYNEAUX et al [25], the authors also observed a new element: a strong association between the presence of specific species of Streptococcus and Staphylococcus and disease progression [28].…”
Section: Ipf and Host-microbiota Interactions And Potential Effects supporting
confidence: 55%
“…Using the data from the COMET-IPF study (Correlating Outcomes with Biochemical Markers to Estimate Time-progression in Idiopathic Pulmonary Fibrosis), HAN et al [28] retrospectively evaluated the role of the microbiota in disease progression. Although the most frequently isolated bacterial species (Prevotella, Veillonella and Escherichia) coincided in part with those identified by MOLYNEAUX et al [25], the authors also observed a new element: a strong association between the presence of specific species of Streptococcus and Staphylococcus and disease progression [28].…”
Section: Ipf and Host-microbiota Interactions And Potential Effects mentioning
confidence: 99%
“…The risk of infection can be reduced by standard infection control measures such as hand washing and vaccination against influenza and pneumococcus. Specific members of the Streptococcus and Staphylococcus genera are associated with IPF progression [69], and the role of the lung microbiome in AE-IPF requires further study. Anti-acid therapy may slow IPF progression and reduce the risk of acute respiratory worsening secondary to aspiration [70], particularly in patients that have subjective symptoms or objective evidence of acid reflux.…”
Section: Managementmentioning
confidence: 99%
“…This new characterization of the lung microbiome is likely to provide important pathogenic insights into chronic lung diseases, including cystic fibrosis, chronic obstructive pulmonary disease, and asthma. Recent papers have reported the possible role of microbiome composition in IPF [13,14]. Increased bacterial burden and presence of specific bacteria have been associated with disease progression.…”
Section: Introductionmentioning
confidence: 99%